Analisis Efektivitas Birokrasi dalam Pelayanan Publik (Studi Kasus Pemerintah Kabupaten Biak Numfor) - Hamjah Bonso; Busyairi Ahmad (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
The existence of bureaucracy is a logical consequence of the main task of the state (government) to organize social welfare. The state is required to be involved in producing goods and services needed by its people (public goods and services), either directly or indirectly. This study aims to determine the effectiveness of the related bureaucracy in public services in the Biak Numfor district government. This study uses the